Cost‐effectiveness of a policy‐based intervention to reduce melanoma and other skin cancers associated with indoor tanning. (18th May 2022) - Eden, Martin; Hainsworth, Rob; Gordon, Louisa G.; Epton, Tracy; Lorigan, Paul; Rhodes, Lesley E.; Marais, Richard; Green, Adele C.; Payne, Katherine
Abstract: Background: The use of indoor tanning devices causes melanoma and other skin cancers with resulting morbidity, mortality and increased healthcare costs. Policymakers require robust economic evidence to inform decisions about a possible ban of such devices to mitigate these burdens. Objectives: To assess the health costs and consequences of introducing a policy‐based intervention across England to ban commercial indoor tanning with an accompanying public information campaign. Methods: A cost‐effectiveness analysis, adopting a healthcare system perspective, was conducted using a decision model to track a national cohort of 18‐year‐olds over a lifetime time horizon. A nationwide ban on commercial indoor tanning combined with a public information campaign (the policy‐based intervention) was compared with the status quo of availability of commercial indoor tanning. The expected costs (currency, GBP; price year, 2019) and quality‐adjusted life‐years (QALYs) were calculated. Net monetary benefit (NMB) (net benefit measured in cost compared with an accepted threshold) and net health benefit (NHB) (net gain in QALYs compared with an accepted threshold) of implementation were calculated. A probabilistic sensitivity analysis was used to calculate the probability that the intervention was cost‐effective. Results: Compared with the current situation, a ban on commercial indoor tanning combined with a public information campaign would result in 1206 avoided cases of melanoma, 207 fewer melanoma deaths and 3987 averted cases of keratinocyte cancers over the lifetime of all 18‐year‐olds ( n = 618 873) living in England in 2019. An additional 497 QALYs would be realized along with healthcare cost‐savings of £697 858. This intervention would result in an NMB of £10.6m and an NHB of 530 QALYS. Multiple sensitivity analyses confirmed the robustness of the findings. At a cost‐effectiveness threshold of £20 000, there is a 99% likelihood of this policy‐based intervention being cost‐effective. Conclusions: The implementation of a ban on commercial indoor tanning across England with an accompanying public information campaign would be an effective use of healthcare resources. Abstract : What is already known about this topic? Melanoma and keratinocyte skin cancers have a significant impact on population health and healthcare budgets, and a proportion are attributable to indoor tanning. Policy‐based interventions that restrict or ban the commercial provision of indoor tanning are in place around the world to reduce the burden of skin cancer, but economic evidence to support decision making is lacking. What does this study add? Banning indoor tanning, supported by a public health campaign, would be an efficient use of healthcare resources to reduce melanoma and keratinocyte cancers in England. This policy‐intervention would save lives (4.6% melanoma deaths avoided) and reduce skin cancer treatment costs with a high degree of confidence. The structured and transparent analysis means that decision makers in other jurisdictions can assess the relevance of these findings to their context. The use of indoor tanning devices causes harm to individuals and increases healthcare costs. A model‐based cost‐effectiveness anlaysis was used to estimate the economic impact of a policy‐based intervention to reduce skin cancers associated with indoor tanning. Implementation of the intervention across England would realise health gains and reduce healthcare costs. Linked Comment: M. Janda and C. Sinclair. Br J Dermatol 2022; 187:7 . Plain language summary available online